Introduction - Krog, Antjie (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
As part of a poetry caravan organised from UWC with international and South African poets, readings were done in four Cape Flats libraries with the poets of that area. Many poems were about rape. Unforgettable still, was a young girl standing with her back to the audience while reading and shivering. A poet from Morocco asked: is rape a big thing in South Africa? It was and it wasn’t. Because it was surfacing in news stories, or as part of testimonies in court cases, it was common knowledge; but it was not in literature. About ten years later, I began to receive more and more manuscripts around this theme, but felt myself swamped with doubt and questions and unable to really assist. How should one write about it? Should it be beautiful? Should the act itself be described? And if so, how that it is not titillating? Should the narrative have a structure? What other texts are there to read that describe a rape as it should or could be described? Is there a ‘blue print’ of how to write abuse? Can one ever write effectively about being beaten? Is that even something to say?